Geological and geophysical expression of a primary salt weld; an example from the Santos Basin, Brazil - Jackson,CA-L; Rodriguez,CR; Rotevatn,A; Bell,RE (Interpretation, 2014)
Primary salt welds form at the base of minibasins in response to complete evacuation of autochthonous salt. Analytical and numerical models suggest it is difficult to completely remove salt from a weld by viscous flow alone, which is especially true in multilayered evaporites, within which flow is likely heterogeneous due to lithologically controlled viscosity variations. Welds are of importance in the hydrocarbon industry because they may provide a hydrodynamic seal and trap hydrocarbons or may allow transmission of fluids from source to reservoir rocks. Few papers document the subsurface expression of welds, principally because of they have not been penetrated or because associated data are proprietary. We use 3D seismic and borehole data from the Santos Basin, offshore Brazil to characterise the geological and geophysical expression of a primary weld associated with the flow of Aptian salt. Seismic data suggest that, locally, presalt and postsalt rocks are in contact at the base of an Upper Cretaceous minibasin, implying that several apparent welds, separated by low-relief salt pillows, are present. However, borehole data indicate that 22 m of anhydrite, carbonate and sandstone are present in one of the welds, indicating that this and other welds may be incomplete. Our study shows that seismic data may be unable to discriminate between a complete and incomplete weld, and we suggest that, during the subsurface analysis of welds, the term ‘apparent weld’ is used until borehole data unequivocally proves the absence of salt. Furthermore, we speculate that preferential expulsion of halite and potash salt from the autochthonous layer during viscous flow and welding resulted in the formation of an incomplete weld, which, when compared to the initial autochthonous layer, is volumetrically enriched in non-evaporite lithologies and relatively viscous evaporite lithologies (anhydrite). The composition and stratigraphy of the autochthonous layer may thus dictate